Role of interfacial tension of solvating diluents and hydrophilic-hydrophobic cross-linkers in hyper-cross-linked solid supports - Mane, Sachin; Ponrathnam, Surendra; Chavan, Nayaku (Industrial & Engineering Chemistry Research, 2015)
The properties of a hyper-cross-linked solid support are the outcome Of the interfacial tension created by solvating/nonsolvating diluents, the hydrophilicity/hydrophobicity of the cross-linkers, and their concentrations. Interestingly, a More hydrophobic diluent and cross-linker as well as a higher concentration of cross-linker-containing copolymer revealed an increase In surface area. A high surface area and low cross-link density (CLD) polymer illustrated higher epoxy content. Importantly, maximum surface area (533 m(2)/g) Was obtained at high CLD; inversely, epoxy,content (1.83 mmol/g) was higher at low CLD polymer. Notably, greater rigidity of cross-linker and its higher concentration increased T-max and T-g; contrarily, greater flexibility of cross-linker and its concentration attenuated T-max and T-g. Thermal study demonstrated the thermostability (300 degrees C) and polymer safe temperature (220 degrees C). Indeed, a lower solubility parameter difference between polymer and swelling solvent produces a higher polymer-solvent interaction parameter, resulting in increased polymer swelling. Polymers with high surface area and low CLD demonstrated greater swelling behavior.

Racemic drug resolution: a comprehensive guide - Mane, Sachin (Analytical Methods, 2016)
The human body is amazingly chirally selective, and consequently enantiopure drugs are essential for treating disease. Nearly 50% of drugs are chiral wherein pharmacological activity resides with the eutomer (pharmacologically active enantiomer) whereas the distomer (inactive/less potent/equally potent/different pharmacological activity/toxic enantiomer) metabolizes by a different pathway and creates unnecessary burden on the body. A teratogenic (toxic) isomer in a racemic drug creates sideeffects, genetic diseases, or may cause death in the case of high dosage. Nowadays, market approval of enantiopure drugs has increased exponentially whereas it has tremendously decreased for racemic and achiral drugs. An expensive process is the main drawback in obtaining enantiopure drugs. Different methods such as chromatography, spectroscopy, and thermal analysis are available for optical purity determination. However, only a few chromatographic methods are useful on an industrial scale. In the present review, racemic resolution and optical purity determination methods are discussed with examples. In addition to this, eutomers and distomers of different drugs containing a single chiral center are also reported.

Role of aliphatic hydrocarbon content in non-solvating porogens toward porosity of cross-linked microbeads - Mane, Sachin; Badiger, Manohar V.; Rajan, C. R.; Ponrathnam, Surendra; Chavan, Nayaku (Polymer, 2016)
Megaporous spherical acrylate copolymer beads were synthesized by suspension polymerization using non-solvating porogens. Non-solvating porogens with higher aliphatic hydrocarbon content generated megaporous morphology with lower surface area. Surface area increased and inversely megaporosity was decreased with decrease in the aliphatic hydrocarbon content of porogen. Megaporosity (5.47 mu m) and pore volume of 5.52 cm(3)/g was obtained with n-decanol. Thermal property of copolymer is a function of type (rigidity/flexibility/elemental composition) and concentration (cross-link density) of monomer and cross-linker. Copolymer containing rigid cross-linker (divinylbenzene) had better thermal stability over copolymer with flexible cross-linker (ethylene dimethacrylate). Further, higher concentration of rigid cross-linker or lower concentration of flexible cross-linker enhanced the thermal stability. Porous polymers are potentially recognized as a solid support for solid-phase synthesis. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Cross-linked microbeads; Interfacial tension; Megaporosity; Non-solvating porogens; Thermal properties